Альтернативна технологія поверхневого зміцнення внутрішніх поверхонь довгомірних деталей - Ляшенко, Б. А.; Лопата, Л. А.; Лопата, В. Н.; Забойкіна, Н. П.; Lyashenko, B.; Lopata, L.; Lopata, V.; Zaboykina, N. (ЦНТУ, 2024)
Розглянуто проблему підвищення живучості стволів танкових гармат шляхом нанесення захисних покриттів. Дана їх коротка характеристика та межі застосування. Однак вирішення проблеми забезпеченні зміцнення, відновлення та підвищення строку служби довгомірних деталей (стволів вітчизняних танкових гармат) існуючими технологіями пов’язано зі складністю підготовки й обробки внутрішньої поверхні (каналу ствола) по всій довжині та виключення можливих залишкових деформацій. Запропоновано альтернативну технологію поверхневого зміцнення електроконтактним припіканням порошкових матеріалів. Ця технологія дозволяє наносити покриття товщиною до 3 мм, з міцністю зчеплення до 200 МПа та щільності, що наближається до щільності компактного матеріалу. Barrel survivability is the main indicator of tank guns. In order to ensure the competitiveness of Ukrainian armored vehicles on the foreign arms market, there was a need to ensure the survivability of the barrels of domestic tank guns at the level of the best world samples. Solving the problem of strengthening, restoring and increasing the service life of long-dimension parts is associated with the complexity of preparing and processing the inner surface (bore) along its entire length and eliminating possible residual deformations. The problem of increasing the survivability of tank gun barrels by applying protective coatings is considered. Their brief characteristics and limits of application are given. An alternative technology for surface hardening by electrical contact sintering of powder materials is proposed. This technology makes it possible to apply coatings up to 3 mm thick, with a density approaching that of a compact material and an adhesive strength of up to 220 MPa. Electrocontact sintering refers to impulse technologies and can exclude further mechanical processing of coatings.
Alternative technology of surface strengthening of internal surfaces of durable parts
Keywords: електроконтактне припікання; зміцнюючі захисні покриття; термін служби; фізико-механічні властивості; electric contact cauterization; strengthening protective coatings; service life; physical and mechanical properties